Histological Studies on Foetal Thyroid Gland of Developing Human Foetuses - Mukhia, Rajeev; Mansur, Dil Islam; Pandey, Mahendra Raj (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: Thyroid gland is the first endocrine gland to develop. It is one of the organs of interest for researchers since a long time. Though, detailed study about adult thyroid is there in the literature but histological study of thyroid gland at different stages in the foetal period is far and few. The present study aims to assess the histogenesis of thyroid gland and also to correlate the functional activity with structural changes in thyroid gland. Methods: The study was carried out on 30 foetal thyroid gland of known gestational age ranging from 10 to 38 weeks foetuses. The midline dissection of neck was done to expose the thyroid gland. After tissue processing, paraffin blocks were prepared. All sections were stained with Haematoxylin-Eosin stain. Results: In the foetuses, below 12th gestational week no colloid was detected in thyroid gland. First appearance of colloid was observed at 14th gestational week. Parafollicular cells were found after 17th gestational week. Capsule thickness and gland vascularity increased with advancement of gestational age. The size of the peripheral follicles is larger than the central follicles. Conclusions: The study concluded the developmental stage of foetal thyroid as Precolloidal stage, Colloid formation stage, Follicular stage and Maturation stage in different gestational weeks. The knowledge on the growth and differentiation of foetal thyroid will be helpful to the clinicians to judge the thyroid structure in preterm babies.